2018
DOI: 10.1002/rmv.2007
|View full text |Cite
|
Sign up to set email alerts
|

Immune function of plasmacytoid dendritic cells, natural killer cells, and their crosstalk in HBV infection

Abstract: Chronic hepatitis B virus infection is a major health problem, with over 245 million chronic carriers worldwide. This persistent infection is thought to be associated with inefficient innate and adaptive immune responses. Natural killer cells (NK cells) and plasmacytoid dendritic cells (pDCs) are the major innate immune cells which respond to viral infection at the early phase and are considered major components of the antiviral immune response. In this review, we summarize recent findings regarding the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…A large number of studies have confirmed that the immune tolerance of chronic hepatitis B virus infection and chronic hepatitis B patients fail to recover from infection due to HBV specific T cell dysfunction. The severity of liver inflammation and viral clearance is related with the specific cytotoxic T lymphocytes (CTL) 8‐10 . However, the role of many other immune cells and their cytokines in clinical pathogenesis and outcome were not well understood 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have confirmed that the immune tolerance of chronic hepatitis B virus infection and chronic hepatitis B patients fail to recover from infection due to HBV specific T cell dysfunction. The severity of liver inflammation and viral clearance is related with the specific cytotoxic T lymphocytes (CTL) 8‐10 . However, the role of many other immune cells and their cytokines in clinical pathogenesis and outcome were not well understood 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Even so, increased secretion of IL-10 upon infection has been reported, which could explain the lack of response described for this virus, as this cytokine will induce a state of tolerance in the surveilling immune cells (305,306). Remarkably, since it has been described that pDCs from HBV infected patients are impaired in their capacities to secrete IFN, this also results in a decreased capacity to induce the proper activation of NK cells (302,307).…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…The roles of NK cells in acute hepatitis B infection have been extensively studied in mice and humans. Early and rapid activation of NK cells has been reported to contribute to HBV clearance, where their dysfunction was associated with the persistence of HBV infection (14). γδT cells are innate immune cells that are not dissimilar to NK cells, which share some common characteristics with regards to virus clearance, including the expression of cytotoxic molecules, including granzyme and perforin, or the production of inflammatory cytokines, including IFN-γ and TNF-α (17).…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune system can respond very rapidly during the early or acute stages of infection to exert functions and boost the subsequent specific immunity. Compared with the extensively studied HBV-specific immunity, mechanisms of innate immune responses during the early stages of HBV infection remain to be defined (1416).…”
Section: Introductionmentioning
confidence: 99%